2003
DOI: 10.1530/eje.0.1490153
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anterior pituitary mitotic response to adrenalectomy after multiple glucocorticoid exposures

Abstract: Objectives: Glucocorticoid withdrawal in man is associated with transient but sometimes prolonged impairment of hypothalamo -pituitary -adrenal axis secretory responsiveness. This has led to continued concern in the clinical arena. The acute anterior pituitary response to glucocorticoids in the rat includes apoptosis-mediated deletion of a cell population. Whilst continued cell turnover following glucocorticoid withdrawal and the potential for differentiation of uncommitted precursor cells and transdifferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The clustering of corticotrophs in the male ANXA1 null pituitary strongly suggests that cell proliferation was the cause of the approximately four‐fold increase in corticotrophs. Corticotroph turnover is dependent on the mitogenic actions of corticotropin‐releasing hormone (CRH) (32–34) and the antiproliferative and pro‐apoptotic actions of glucocorticoids (35). The striking increase in corticotrophs in male ANXA1 null mice initially suggested that in males, but not females, a lack of ANXA1‐mediated glucocorticoid feedback at the hypothalamus (36) had increased CRH secretion causing proliferation of corticotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…The clustering of corticotrophs in the male ANXA1 null pituitary strongly suggests that cell proliferation was the cause of the approximately four‐fold increase in corticotrophs. Corticotroph turnover is dependent on the mitogenic actions of corticotropin‐releasing hormone (CRH) (32–34) and the antiproliferative and pro‐apoptotic actions of glucocorticoids (35). The striking increase in corticotrophs in male ANXA1 null mice initially suggested that in males, but not females, a lack of ANXA1‐mediated glucocorticoid feedback at the hypothalamus (36) had increased CRH secretion causing proliferation of corticotrophs.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone (0.3 ml; approximately 50 µg/100 g) was administered subcutaneously between 16.00 h and 19.00 h for the first 3 consecutive days after ADX. The treated rats also received dexamethasone in their drinking water [0.75 µg/ml dexamethasone in 0.9% (w/v) saline available ad libitum ] after ADX until they were sacrificed; modified from (19). Five days after surgery, the same procedures as experiment 1 were used to sacrifice all animals and prepare hypothalamic sections.…”
Section: Methodsmentioning
confidence: 99%